A study of Ophthalmia Neonatorum in the Central Reion of Ghana: Causative Agents and Antibiotic Susceptibility Patterns - Samuel Bert Boadi-Kusi OD, Ph.D; Samuel Kyei OD, Ph.D; Selina Holdbrook OD; Emmanuel Kwasi Abu OD, Ph.D; Jonathan Ntow Bsc; Abena Mantebea Ateko OD (SAGE Publishing, 2021)
In developing countries such as Ghana, ophthalmia neonatorum (ON) remains a public health concern. This is because of its unknown etiology patterns, the growing concerns of antibiotic resistance strains and the contribution of ON to childhood blindness. This study was therefore conducted to determine the causative agents, risk factors and the antibiotic sensitivity patterns of micro-organisms associated with ON. A clinic-based prospective study was conducted in the Maternal and Child Health units of six health care facilities in the Central region of Ghana over a period of 17 months. Conjunctival swabs were taken from all neonates with clinical signs of ON. Isolation and characterization of bacteria were done using standard microbiological methods. Additionally, data were collected and analyzed on neonate's demographics and clinical features of ON. Microbial growth was recorded in 86 cases (52.4%) out of the 110 neonates assessed. Staphylococcus spp. (39.2% of all positive cultures) was the most common causative organism. No case of gonococcus was isolated. Delivery method, vaginal discharge, administration of prophylaxis and weight of neonate were the risk factors associated with the development of ON ( P  < .05). The level of resistance to Tetracycline was found to be 73%. Neonatal conjunctivitis is more likely to be acquired postnatal. Culture and sensitivity testing are required as an important guide for treatment. The commonest causative organism, Staphylococcus spp., were found to be resistant to Teteracyline which is currently being used as prophylaxis in the prevention of ON. There is therefore the need to consider alternative measures in the prevention and control of ON.